2006
DOI: 10.1002/hep.21355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clonidine on diuretic response in ascitic patients with cirrhosis and activation of sympathetic nervous system

Abstract: The effects of the addition of clonidine to diuretics on the mobilization of ascites in the short term (diuretic response and requirement of diuretics) and the long term (readmissions for tense ascites and requirement of diuretics) were examined in patients with cirrhosis and with increased sympathetic nervous system (SNS) activity. We also studied neurohormonal, hemodynamic effects and side effects of clonidine and diuretics. Patients were randomized to receive placebo (group1, n ‫؍‬ 32) or clonidine (0.075 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 81 publications
1
47
1
3
Order By: Relevance
“…First is the combination of diuretics with drugs that improve the circulatory function or suppress the increased activity of antinatriuretic systems. In this regard, a recent study showed that the combination of diuretics with oral clonidine (0.75 mg twice daily), a drug that suppresses the activity of the sympathetic nervous system (which is markedly increased in patients with refractory ascites), led to a more rapid mobilization of ascites with fewer complications than placebo in patients with cirrhosis, ascites, and a plasma norepinephrine level greater than 300 pg/mL [17]. In another study, the administration of oral midodrine (an alpha-1 adrenergic agonist), 10 mg three times daily for 7 days, to patients with cirrhosis and ascites was associated with increased natriuresis and glomerular filtration rate and improvement in circulatory function with suppression of antinatriuretic systems (ie, renin-angiotensin-aldosterone system) [18].…”
Section: Consider Use Of Transjugular Intrahepatic Portosystemic Shunmentioning
confidence: 96%
“…First is the combination of diuretics with drugs that improve the circulatory function or suppress the increased activity of antinatriuretic systems. In this regard, a recent study showed that the combination of diuretics with oral clonidine (0.75 mg twice daily), a drug that suppresses the activity of the sympathetic nervous system (which is markedly increased in patients with refractory ascites), led to a more rapid mobilization of ascites with fewer complications than placebo in patients with cirrhosis, ascites, and a plasma norepinephrine level greater than 300 pg/mL [17]. In another study, the administration of oral midodrine (an alpha-1 adrenergic agonist), 10 mg three times daily for 7 days, to patients with cirrhosis and ascites was associated with increased natriuresis and glomerular filtration rate and improvement in circulatory function with suppression of antinatriuretic systems (ie, renin-angiotensin-aldosterone system) [18].…”
Section: Consider Use Of Transjugular Intrahepatic Portosystemic Shunmentioning
confidence: 96%
“…Clonidine, a centrally acting α 2 -agonist and sympatholitic agent, was evaluated as an adjunct treatment in patients with cirrhosis and ascites. In a randomized study, oral clonidine (0.075 mg, two times daily) led to a more rapid mobilization of ascites with fewer complications than placebo in patients with cirrhosis, ascites, and a plasma norepinephrine level of >300 pg/ mL [75]. This medication was also evaluated in a randomized study of clonidine plus diuretics versus diuretics alone which showed that the highest efficacy was obtained in patients who had high serum levels of norepinephine and the presence of two specificgenetic polymorphisms that predicted clonidine response in cirrhotic patients [76].…”
Section: Initial Managementmentioning
confidence: 99%
“…In a randomised controlled trial, clonidine combined with spironolactone was more effective than spironolactone alone, with a more rapid clinical response and reduced diuretic requirement. 13 Adverse effects include postural hypotension, dry mouth, fatigue, drowsiness and erectile dysfunction.…”
Section: α-Adrenoceptor Agonistsmentioning
confidence: 99%